Conceptual aspects of multi-criteria decision-making in management activity - HRYNCHAK, N. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The activities of enterprises in conditions of instability of the external environment, high rates of technical progress and processes of globalization create many complex problems for them, the solution of which requires the adoption of balanced and effective management decisions. Decision-making is one of the most important elements of managing the development of an enterprise, both in the short-term and in the long-term. In this regard, there is an intensive development of various tools and methods of the management decision-making process. The conceptual aspects of multi-criteria decision-making are considered in the article. The essence of the multi-criteria decision-making method was determined, the scope of its application was investigated. It is substantiated that in the process of multi-criteria decision-making, a significant number of criteria are considered, however, to make an optimal decision, all alternatives must have common criteria that directly affect the solution of a specific problem and lead to the adoption of a better decision. The methods of multi-criteria decision-making are distinguished and characterized. It was determined that considering the rapid, dynamic, sometimes chaotic development of the external business environment, in which effective management decision-making will be based on considering an increasing number of various factors, the specifics of the practical application of various methods of multi-criteria decision-making require further research.